Penerapan Terapi Murottal Al-Quran Terhadap Kecemasan Pada Pasien Yang Menjalani Hemodialisis - Kesyia Ayuni Asnidatama; Ida Nurjayanti; Agus Rismanto (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Chronic kidney failure refers to the decline in kidney’s ability to maintain body fluid balance. Hemodialysis, as a kidney function replacement therapy, is needed to remove toxins and control electrolyte fluids in the body. One of the psychological impacts of hemodialysis is anxiety in patients. One way to reduce patient anxiety levels is by conducting murottal Al-Qur’an therapy. This study uses a case report method and was conducted in the Hemodialysis room of PKU Muhammadiyah Yogyakarta from May 2 to May 9, 2024. Two people with a diagnosis of chronic kidney failure were respondents in this study. The Hamilton Anxiety Rating Scale (HARS) was used as an instrument in this study, which was conducted before and after intervention. The results of the study showed that the respondents’ anxiety scores were in the moderate category (24 and 23) and changed to the mild category with a score of 14 after the application of therapy. This therapy has proven effective in reducing anxiety levels in patients with chronic kidney failure who are undergoing hemodialysis therapy.